Analisis Kesulitan Belajar Maharoh Kalam Pada Mata Kuliah Bahasa Arab Mahasiswa Jurusan Pendidikan Agama Islam Institut Agama Islam Tarbiyatut Tholabah Lamongan - Ratih Kusuma Ningtias (Darajat: Jurnal Pendidikan Agama Islam, 2021)
Learning cannot be separated from problems including learning difficulties. This paper discusses learning difficulties related to maharoh kalam in Arabic language courses for students majoring in Islamic Religious Education at the Tarbiyatut Tholabah Islamic Institute, which in its discussion consists of the terminology of learning difficulties, the factors Learning Difficulty Factors, Learning Difficulty Symptoms, Arabic Language Learning are associated with Maharoh Kalam in Students of the PAI IAI Tabah Department. The difficulty factor for learning kalam in Arabic courses faced by PAI students class of 2019 lies in a lack of motivation, not mastering Arabic vocabulary, the factor of graduating from public schools is one of the factors of difficulty encountered. The motivation to do so that learning Arabic can be learned easily is by practicing a lot, memorizing a lot of vocabulary and also starting to get used to conversations using Arabic